COVERAGE OF HEALTH INSURANCE: A STUDY ON NORTH-EASTERN STATES OF INDIA WITH SPECIAL REFERENCE TO ASSAM - Sabhapandit, Monikankana; Phukan, Khirod Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Health insurance becomes an effective measure to reduce poverty, which is the core constraint of sustainable development. Though various types of social health insurance schemes are introduced in India, most of the nation, particularly the northeastern states with special reference to Assam, have very limited coverage under the health insurance schemes. The study aims to analyse health insurance coverage in the rural and urban sectors of northeastern states and Assam and to find the association between various household types covered under different types of health insurance schemes. In addition, regional variations in coverage of health insurance are examined in the study. The study will be based on secondary data only. Data is being collected basically from the unit-level record of the 75th round (2017-18) of the National Sample Survey published by the Government of India, Ministry of Statistics and Program Implementation. Independent sample t-test, Phi, and Cramer’s V test are used to analyse the objectives. The coverage of health insurance is not adequate in Rural and Urban Assam. The occupation of the household is associated with the coverage of the health insurance programme.